2014
DOI: 10.1590/s1519-99402014000200003
|View full text |Cite
|
Sign up to set email alerts
|

Tendências, parâmetros fenotípicos e genéticos de características de crescimento em bovinos Nelore mocho do Nordeste brasileiro

Abstract: Objetivou-se estimar parâmetros e avaliar a tendência fenotípica e genética de pesos ajustados para 205 (P205); 365 (P365) e 550 (P550) dias de idade, em bovinos da variedade Nelore Mocho, nascidos a partir de 1980, pertencentes a rebanhos localizados na região Nordeste do Brasil. Foram utilizados registros genealógicos de 45.785 animais nascidos entre 1960 e 2009. Os parâmetros e os valores genéticos foram estimados com o método de máxima verossimilhança restrita livre de derivadas (REML) sob o modelo animal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
3
0
8
Order By: Relevance
“…A more significant increase was then observed up to older ages (Figure 1). Similar results were observed by Amaral et al (2014) who evaluated the growth of Nellore cattle in the Northeast of Brazil.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A more significant increase was then observed up to older ages (Figure 1). Similar results were observed by Amaral et al (2014) who evaluated the growth of Nellore cattle in the Northeast of Brazil.…”
Section: Resultssupporting
confidence: 87%
“…These employ multi characteristics to provide animal weight information and do not require standardization or pre adjustments El Faro, 2008;Baldi et al, 2010;Sousa Júnior et al, 2010). To adjust randomregression models, a covariance matrix of infinite size is required and an effective alternative is the use of covariance functions.…”
Section: Introductionmentioning
confidence: 99%
“…Lacerda et al (2014) estimaram ganhos de 0,06 kg/ano; 0,03 kg/ano e 0,04 kg/ano, para P205, P365 e P550, respectivamente, em bovinos da raça Nelore no estado da Bahia. Enquanto que progresso genético inferior foi relatado na raça Nelore Mocho em todo o Nordeste Brasileiro por Amaral et al (2014), que estimaram tendências genéticas diretas de 0,01; 0,04 e 0,04 kg/ano, para P205, P365 e P550 respectivamente.…”
Section: Resultsunclassified
“…Resultados próximos também foram relatados na raça Nelore, no estado da Bahia, por Lacerda et al (2014), com progressos estimados de 1,13 kg/ano (P205), 1,25 kg/ano (P365) e 1,69 kg/ano (P550). Por outro lado, Amaral et al (2014) estimaram ganhos fenotípicos superiores para P365 (2,10 kg/ano) e P550 (2,84 kg/ano) na raça Nelore Mocho no Nordeste.…”
Section: Resultsunclassified
“…Evaluating Pooled Nellore in the northeast of Brazil, Amaral et al (2014) estimated heritability of 0.19 for weight adjusted to 205 days in single trait analysis. Araújo et al (2014) reported estimates of 0.36 for weight at 210 days in Nellore cattle.…”
Section:    mentioning
confidence: 99%